My Apparel : uniform manufacturing for hotels and restaurants / Fazlinur Mustaqim Hussain ... [et al.] - Hussain, Fazlinur Mustaqim; Mohamad Wan, Norsuhada; Mohamad, Asrul Hairi; Jibril, Nur Hazwani (Faculty of Hotel and Tourism Management, 2006)
There is still room for one more business of producing uniforms around Petaling Jaya, specifically for hotel's and restaurant's use. So far there are more non- Bumiputera owned businesses in the field, but with intense research and careful planning, we are confident that we still have the competitive edge in getting the attention and share of market. Our company is named as MyApparel and it will be commence in 1st January 2OO7.We decided to have our establishment placed in Petaling Jaya district because we found that there is a large market for uniforms in this area. There are plenty of hotels and restaurants erected and the combined workforce who requires uniform is pretty big, totaling around RM 7.8 million in sales estimated by considering that each worker will have to have three uniforms of the same kind.